(untitled) (Heritage, 2022)
This work is an attempt to present integrative teaching as an innovative model, to point out its advantages and great possibilities in teaching as well as to determine its application in teaching Nature and society. Our task was to draw attention to the importance of applying integrative model in teaching Nature and society and to the contents of certain spheres of teaching that can be integrated through this teaching subject. Active role of students in the process of teaching is widely insisted upon nowadays, because of which teachers are expected to choose contents, activities or certain models which will be the most efficient in realization of the teaching process. In accordance with the defined topic and the research subject, objects and tasks, as well as the study of relevant literature, we pointed out that the topic is extremely actual and important for teaching Nature and society, especially for theory and practice within the subject. The research showed that contents integration offers teachers the possibility to find authentic ways to join different aspects of the teaching material, by which the contents are interpreted and presented in an interesting and meaningful way.